2009
DOI: 10.1111/j.1600-6143.2009.02736.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cariporide with Glyceryl Trinitrate Optimizes Cardiac Preservation During Porcine Heart Transplantation

Abstract: Sodium-hydrogen exchange inhibitors, such as cariporide, are potent cardioprotective agents, however, safety concerns have been raised about intravenously (i.v.) administered cariporide in humans. The aim of this study was to develop a preservation strategy that maintained cariporide's cardioprotective efficacy during heart transplantation while minimizing recipient exposure. We utilized a porcine model of orthotopic heart transplantation that incorporated donor brain death and 14 h static heart storage. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Our group has previously reported that glyceryl trinitrate, erythropoietin and zoniporide, when added as single or combined supplements to C solution, activate the same intracellular kinases that mediate ischemic preconditioning and postconditioning (14)(15)(16)(17). We have further shown that supplementing C solution with these agents reduces IRI in an isolated working rat heart model (16) and in an NDD porcine transplant model (18).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our group has previously reported that glyceryl trinitrate, erythropoietin and zoniporide, when added as single or combined supplements to C solution, activate the same intracellular kinases that mediate ischemic preconditioning and postconditioning (14)(15)(16)(17). We have further shown that supplementing C solution with these agents reduces IRI in an isolated working rat heart model (16) and in an NDD porcine transplant model (18).…”
Section: Discussionmentioning
confidence: 75%
“…The chest cavity was subsequently filled with cold saline slush. In the ''supplemented'' groups (Cs), pharmacological agents known to activate ischemic conditioning pathways (14)(15)(16) were added to the C solution. These supplements and their doses are listed in Table 1.…”
Section: Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“…If this is the case then a combination of pretransplant immunoabsorption, cardiac preconditioning (49) or pharmacological treatments to improve cardiac resistance to I/R injury (50, 51) may modulate PCXD. Genetic modification to increase adenosine receptor (52) and CD39 expression (53) in the heart or to increase the number of collateral arteries (54) might also alleviate PCXD.…”
Section: Orthotopic Cardiac Xenotransplantationmentioning
confidence: 99%
“…An Australian group demonstrated that glyceryl trinitrate, erythropoietin, and zoniporide are mediators of pre and post conditioning at the enzymatic level. 21ā€“23 They attempted to use these agents to limit the detrimental effects of warm ischemia in a porcine model of donation after circulatory death (DCD). They were able to show improvement in the tolerance to warm ischemia based on improvement in return of electromechanical function, and a decrease in biomarkers indicative of myocardial injury including lactate.…”
Section: Discussionmentioning
confidence: 99%